THE MORPHOTECTONIC CHARACTERISTIC OF BUOL WATERSHED AND IMPLICATION TO SPATIAL PLANNING IN BUOL REGION, CENTRAL SULAWESI, INDONESIA - Tawil, Sukardan; Sukiyah, Emi; Rosana, Mega Fatimah; Muslim, Dicky; Raditya Rendra, Pradnya Paramarta (Journal of Geological Sciences and Applied Geology, 2019)
The Buol watershed is located on the northern arm of Sulawesi Island. Geomorphology in this region is controlled by developing faults. Geomorphological analysis is done to obtain objective results. Geomorphological variables can explain significantly the geomorphic process itself. The studio, field and laboratory methods is used in this research. Studio analysis consists of topographical map, satellite imagery, Ratio of valley Floor Width to Valley Height (Vf), Mountain Front Sinuosity (Smf), Drainage density (Dd), and Bifurcation Ratio (Rb) analysis. Also, statistical test is used to determine the relationship between these variables. Research area in watershed Buol has landform, namely lowland, low hills, hills, and high hill. Drainage pattern that developed namely anastomotic, sub-dentritic, sub-parallel, trellis, and sub-trellis drainage pattern. The results of the watershed morphometry analysis show calculation of the average value of Rb is 1.48 to 6.24, value of Dd average from 1.17 to 2.45., Smf value ranged from 1.6 to 1.76 and Vf ratio range from 0.5 to 1. That phenomenon shows that the Buol watershed is controlled by tectonic.